Impact of Body Mass Index on Outcomes of Cervical Cerclage: A Systematic Review and Meta-Analysis - Lihua Yang; Hua Yang (Obesity Facts)
Introduction: The purpose of the review was to examine the impact of maternal body mass index (BMI) on outcomes of cervical cerclage for cervical insufficiency. Methods: This prospectively registered review (CRD42024512436) searched PubMed, Embase, Scopus, and Web of Science for comparative studies published before 6 March 2024. Maternal and neonatal outcomes of females undergoing cerclage were compared based on BMI. Results: Seven studies were included. Pooled data showed that the risk of preterm birth (PTB) (<37 weeks) was significantly increased in the obese vs. non-obese group (odds ratio 1.32, 95% confidence interval [CI]: 1.15, 1.51; I2 = 36%). Gestation age at delivery in weeks was also found to be significantly lower in the obese group (MD: −2.47, 95% CI: −4.83, −0.12; I2 = 96%). There was no significant difference in the risk of preterm premature rupture of membranes and chorioamnionitis between the two groups. Still, the rate of cesarean sections was significantly higher in the obese group. Neonatal birth weight in grams was not found to be significantly different between obese and non-obese groups but the risk of neonatal intensive care unit (NICU) admission was significantly increased in the obese group. Conclusion: Low-quality evidence indicates that obesity may lead to an increased risk of PTB in women undergoing cervical cerclage. The risk of cesarean section and NICU admission is also increased in obese females.